2018
DOI: 10.1016/j.pnpbp.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine use may induce telomere shortening in individuals with HIV infection

Abstract: Our findings suggest that cocaine use may promote premature aging in HIV-infected individuals who are on ART. Our results emphasize the importance of cocaine abstinence/reduced use, which may retard HIV-associated premature aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Yang et al reported that drug abusers overall had reduced LTL, but when they classified the drugs of abuse into depressant drugs, stimulant drugs, and hallucinogenic drugs they found those taking stimulant drugs (such as METH and methylenedioxymethamphetamine [MDMA]) did not exhibit shorter LTLs [30]. In contrast, reports in cocaine users demonstrated that cocaine use promotes the shortening of telomere length [31,32]. Furthermore, cocaine abusers reporting a history of childhood abuse and neglect displayed significantly shorter telomeres than those without such history [32], suggesting adverse childhood experiences (ACEs) might contribute to the shortening of LTL in drug abusers.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported that drug abusers overall had reduced LTL, but when they classified the drugs of abuse into depressant drugs, stimulant drugs, and hallucinogenic drugs they found those taking stimulant drugs (such as METH and methylenedioxymethamphetamine [MDMA]) did not exhibit shorter LTLs [30]. In contrast, reports in cocaine users demonstrated that cocaine use promotes the shortening of telomere length [31,32]. Furthermore, cocaine abusers reporting a history of childhood abuse and neglect displayed significantly shorter telomeres than those without such history [32], suggesting adverse childhood experiences (ACEs) might contribute to the shortening of LTL in drug abusers.…”
Section: Introductionmentioning
confidence: 99%
“…S-acylated Rif1 mediated by palmitoyl acyltransferase Pfa4 mounts a localized DNAdamage response proximal to the inner nuclear membrane and promotes telomere homeostasis [59]. Longitudinal analyses of 147 HIV-infected participants in Baltimore between June 2010 and December 2016 suggested that cocaine use induced/accelerated telomere shortening in HIV-infected individuals [60]. Then, local anesthetics may also mediate the telomere homeostasis of cancer stem cells through ZDHHC15 or palmitoylation modification.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that shorter LTLs in HIV + individuals were strongly associated with advancing age, cART without INSTI, failure to achieve viral control after initiation of cART, and substance use. In previous reports, cART and substance abuse have sometimes been associated with LTL shortening in HIV + individuals [25, 26]. Antiretroviral drug-induced toxicity is an important complication of cART, particularly for regimens containing protease inhibitors (PIs).…”
Section: Discussionmentioning
confidence: 99%